2020
DOI: 10.2147/ndt.s247787
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Expression and Genetic Variation of microRNA-34b/c on Cognitive Dysfunction in Patients with Major Depressive Disorder</p>

Abstract: Background: Patients suffering from major depressive disorder (MDD) commonly demonstrate lower performance across multiple cognitive domains. Cognitive impairment is an intrinsic characteristic of MDD status and is often influenced by genetic factors. microRNAs (miRNAs or miRs) have been shown to have important implications in the etiology of MDD. Therefore, we aimed to identify and analyze the impact of expression and genetic variation of miR-34b/c on cognitive dysfunction in MDD. Methods: First, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Eight weeks of paroxetine and 12 weeks of escitalopram treatment normalized levels of miR-34a-5p in serum [ 111 ] and miR-34c-5p levels in whole blood [ 94 ]. Interestingly, the levels of blood miR-34c-5p were significantly negatively correlated with language and delayed memory index scores in MDD, but not healthy patients [ 152 ], which may suggest that alterations in the expression of the miR-34 family may contribute to decreased cognitive functions observed in depression.…”
Section: From Changes In the Brain To Changes In The Periphery: A Summarymentioning
confidence: 99%
“…Eight weeks of paroxetine and 12 weeks of escitalopram treatment normalized levels of miR-34a-5p in serum [ 111 ] and miR-34c-5p levels in whole blood [ 94 ]. Interestingly, the levels of blood miR-34c-5p were significantly negatively correlated with language and delayed memory index scores in MDD, but not healthy patients [ 152 ], which may suggest that alterations in the expression of the miR-34 family may contribute to decreased cognitive functions observed in depression.…”
Section: From Changes In the Brain To Changes In The Periphery: A Summarymentioning
confidence: 99%
“…Regardless of sex, our data show a significant increase in PFC miR-20b-5p. A previous study showed that blood levels of miR-34c-5p decreased with improved cognitive and memory performance in depressed individuals [ 41 ]. Similarly, we found increased miR-34c-5p expression in MS animals.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30 family seems also interesting now that certain polymorphic variants such as miR-30e increase MDD susceptibility and others are biomarkers of late life depression (miR-30d) and PSD (miR-30a-5p) [ 181 , 182 , 183 , 184 ]. We find more variants of susceptibility for miR-34: rs4938723/rs28757623 polymorphisms affecting miR-34b/c genes are potential risk factors for suffering from MDD; moreover, MiR-34a is differentially expressed in MDD, bipolar disorder and schizophrenia in the anterior cingulate cortex [ 70 , 185 , 186 , 187 , 188 ]. More specifically, some variations of miR-504, rs686, affecting DRD1 regulation, have been found associated with higher depression scales [ 76 , 189 ].…”
Section: Mirnas With Diagnostic Prognostic and Predictive Valuementioning
confidence: 99%
“…Certain polymorphisms in miR-34 are categorized as more severe and related to suicide idea and cognitive dysfunction. For example, the polymorphism rs2187473 affecting miR-34c is a potential genetic risk factor for cognitive decline in MDD, as well as peripheral blood leukocytes levels of miR-34b and miR-34c were related to suicide idea [ 188 ]. MiR-137 was found downregulated by 25% in postmortem prefrontal cortex of depressed patients with suicidal behavior but further prognostic proposals have not been yet exploited [ 198 ].…”
Section: Mirnas With Diagnostic Prognostic and Predictive Valuementioning
confidence: 99%